Colonization founding myths in Latin American culture and literature: indigenism as a reaction to the colonial ethnocentrism of Indianism: Dos mitos fundadores da colonização na cultura e na literatura latino-americana: o indigenismo como reação ao etnocentrismo colonial do indianismo (Revista de História da UEG (REVHIST), 2024)
This essay is designed to analyze the process of building the literary imaginary in Latin America based on the founding myths named in this text as the triad of the imaginary, consolidated in the image of the indigenous person (SMITH, 1624), the colonizer (AMATE BLANCO, 1981) and the image of the land in the context of literary cartography (AINSA, 1992). In this process, it is argued that these myths can be found in two perspectives: the colonial one through accommodation to the desires of the hegemonic classes that characterized romantic Indianist literature and the counter-hegemonic movement proposed by indigenist fiction. In order to study the process of capturing these myths/mythemes in indigenous literature, we draw on Durand's (2002) conceptions through the anthropology of the imaginary in the process of modeling by capture and/or by anti-modeling through the theories of Kothe (1981) in the works Iracema (ALENCAR, 2003) in Romantic Indianism and Raza de Bronce in Alcides Arguedas' Indigenism (2001).Keyword: Latin American and cultures literature. Founding myths. Indianism. Indigenism. Modeling.